Induction therapy confers survival advantage in mechanically supported patients regardless of peak CPRA in heart transplantation - Nataliya Bahatyrevich, MD, MS; Reid Dale, PhD; Matthew Leipzig, BSc; Katharine Casselman Pines, MPH; Shirin Jimenez, MD; Maria Currie, MD, PhD (JHLT Open)
Background: There is no consensus regarding induction therapy in patients on mechanically circulatory support (MCS) listed for heart transplantation. We sought to elucidate differences in outcomes between no induction and induction. Methods: A total of 3,987 patients were analyzed from the UNOS database from January 2018 through December 2022. Patients on Extracorporeal Membrane Oxygenation (ECMO), HeartMate 3, Impella 5.0 or 5.5, and intra-aortic balloon pump (IABP) and receiving no induction, anti-IL2R antibodies, or T cell depleting agent (TCDA) were included. Results: Of 3,987 patients, 1,288 (32.3%) received no induction, 1,566 (39.3%) received anti-IL2R antibodies, and 1,133 (28.4%) received TCDA. A total of 1,895 (47.5%) were supported with IABP; 1,098 (27.5%) with HeartMate 3; 489 (12.3%) with Impella 5.0 or 5.5; 351 (8.8%) with ECMO; and 154 (3.9%) with combination of the above devices. Comparison of 1-year survival between no induction, anti-IL2R, and TCDA groups in all MCS patients revealed significantly worse survival among those receiving no induction (p<0.0001). Subgroup analysis of peak CPRA 0% patients revealed that no induction had significantly worse survival at 1 year (p=0.002). Analysis of acute rejection at 1 year showed a significantly decreased number of rejection episodes in the TCDA group compared to no induction (OR 0.65, CI 0.47-0.88, p=0.006). Conclusions: Patients requiring MCS prior to heart transplantation have significantly improved post-transplant survival with induction therapy, regardless of their peak CPRA. TCDA confers decreased number of acute rejection episodes at 1 year in this patient population.